2019
DOI: 10.5267/j.msl.2019.7.033
|View full text |Cite
|
Sign up to set email alerts
|

The role of transformational leadership style in enhancing employees’ competency for organization performance

Abstract: The transformational leadership style as practiced by the organization leaders was examined in their role to enhance employees' competency for organization performance. A quantitative approach is used in this study using a survey approach through the distribution of a set of questionnaires. In this study, the sample comprised of 232 supervisors from three food manufacturing industries in various supervisory levels, departments, and sections within the production line. The hypotheses were analyzed using IBM Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…Relatively, Karemu, Kachori, Josee, and Okibo (2014) found that a positive relationship exists between recruitment and organizational performance. In line with that, in the recent work of Atan and Mahmood (2019), employee competency in connection with effective recruitment has greater role in organizational performance and plays a vital role in every organization (see Abubakar, Ilkan, Al‐Tal, & Eluwole, 2017; Elci, Abubakar, Ilkan, Kolawole, & Lasisi, 2017).…”
Section: Introductionmentioning
confidence: 68%
“…Relatively, Karemu, Kachori, Josee, and Okibo (2014) found that a positive relationship exists between recruitment and organizational performance. In line with that, in the recent work of Atan and Mahmood (2019), employee competency in connection with effective recruitment has greater role in organizational performance and plays a vital role in every organization (see Abubakar, Ilkan, Al‐Tal, & Eluwole, 2017; Elci, Abubakar, Ilkan, Kolawole, & Lasisi, 2017).…”
Section: Introductionmentioning
confidence: 68%
“…Scholars have attempted to identify leadership styles that are suited for encouraging innovation in their efforts to understand the link between leadership and innovation. Some authors claim that supportive, participative, visionary, democratic, and collaborative leadership styles are effective in encouraging innovation (Zheng et al, 2019), while others claim that transformational leadership is the best style for promoting innovation (Alqatawenh, 2018;Alzahrani, 2019;Atan & Mahmood, 2019).…”
Section: Literature Review Leadershipmentioning
confidence: 99%
“…The competencies related to self-awareness contain emotional self-awareness, which deals with recognizing own feelings and emotions, as well as the effects of them. Self-awareness can be likely to have positive relation with managerial effectiveness (Atan et al 2019). Characteristics like team spirit, workplace productivity, and delegation of authority, empowerment and effective communication skills are considered for managerial effectiveness.…”
Section: Role Of Emotional Intelligence To Enhance Managerial Effectivenessmentioning
confidence: 99%